Edukasi Kesehatan pada Siswa Sekolah Dasar “Katakan Tidak pada Bullying: Bersama Kita Bisa” - Febby Anggraeni Rochmah; Ressa Julliyana; Veny Oktaviany; Reni Nuryani; Sri Wulan Lindasari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying among elementary school students is a serious problem that significantly impacts various aspects of children’s lives, including mental health, emotional development, and academic achievement. This community service program, in the form of Health Education with the theme “Say No to Bullying: Together We Can!” and the development of the UKS Jiwa program as an extension of the existing UKS, aims to increase students’ knowledge and awareness about bullying and its prevention through a health education approach using a quantitative method with a pre-experimental one-group pretest-posttest design. The activity was conducted on November 29, 2024, at SDN Citepok, Paseh District, Sumedang Regency, involving 61 students from grades 4, 5, and 6 as the main participants, with teachers supporting the program’s sustainability. The educational materials were developed based on scientific sources and official handbooks from the Ministry of Education and Culture, covering the definition, types, impacts, and prevention strategies of bullying, and were delivered through lectures, animated videos, interactive discussions, simulations, and case analyses. The effectiveness of the intervention was measured using valid and reliable pre-test and post-test instruments. The results of the analysis showed a significant increase in students’ knowledge after the intervention, with all participants achieving a good level of knowledge in the post-test. This intervention not only improved students’ understanding of bullying but also fostered supportive attitudes and behaviors to create a safe and inclusive school environment. This health education program is recommended to be continuously integrated into the UKS program and the elementary school curriculum as an early effort to prevent bullying.